2008
DOI: 10.1016/j.juro.2007.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stenting and Urinary Stone Management: A Systematic Review

Abstract: Stenting is not mandatory after uncomplicated simple ureteroscopy and shock wave lithotripsy. Patients with stents seem to have significantly more bladder and lower urinary tract symptoms than those in whom stents are not placed. However, there is a subgroup of patients who likely benefit from stenting following a procedure because of the increased risk of complications. The ideal ureteral stent biomaterial has yet to be discovered and an area of promising development is the drug eluting stent to prevent infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 47 publications
2
147
0
3
Order By: Relevance
“…Although several randomized prospective trials showed that use of JJ stents after uncomplicated URS was unnecessary and carried a higher postoperative morbidity, many urologists use JJ stents routinely after URS. [16][17][18] Studies comparing URS sizes in children reported a higher JJ stent insertion rate after smallcalibre URS. [5,6,15] In adult patients, Yaycıoğlu et al [4] reported higher stenting rates after small-calibre ureteroscopy, however Atis et al [7] emphasized a reduction in postoperative rate of stent use.…”
Section: Discussionmentioning
confidence: 99%
“…Although several randomized prospective trials showed that use of JJ stents after uncomplicated URS was unnecessary and carried a higher postoperative morbidity, many urologists use JJ stents routinely after URS. [16][17][18] Studies comparing URS sizes in children reported a higher JJ stent insertion rate after smallcalibre URS. [5,6,15] In adult patients, Yaycıoğlu et al [4] reported higher stenting rates after small-calibre ureteroscopy, however Atis et al [7] emphasized a reduction in postoperative rate of stent use.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha blockade is associated with decreased stent related morbidity and smaller studies have shown benefit of anticholinergic medication. Other experimental approach is to decrease bladder urothelium irritation by intravesical submucosal injection of local anaesthetic or by developing stents with a soft distal coil [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, some ureters are unable to respond to foreign body insertion with increased peristalsis amplitude and remained decompensated (B). There are still controversial opinions on the necessity of stent indwelling and corresponding indications for ureteral stenting for the patients subjected to ureteroscopy and lithotripsy (Venkatesh et al, 2005;Haleblian et al, 2008). Clinical examinations of the patients did not reveal any difference in the results of stent indwelling despite the differences in the character of the contractile function manifested by pronounced or aberrant peristalsis.…”
Section: Effect Of Stents On Ureteral Performancementioning
confidence: 93%